Should Thoracolumbar Junction Be Always Avoided as Upper Instrumented Vertebra in Long Instrumented Fusion for Adult Spinal Deformity?: Risk Factor Analysis for Proximal Junctional Failure. Issue 10 (15th May 2020) - Park, Se-Jun; Lee, Chong-Suh; Park, Jin-Sung; Lee, Kyung-Jun
Abstract : Study Design: Retrospective study. Objective: The aim of this study was to investigate the risk factors for proximal junctional failure (PJF) following long instrumented fusion stopping at thoracolumbar junction (TLJ) in adult spinal deformity (ASD) and to determine which cases are suitable for TLJ stop without increasing the risk for PJF. Summary of Background Data: PJF following long fusion for ASD is a well-recognized complication that negatively affects clinical outcomes. Generally, the uppermost instrumented vertebra (UIV) at the TLJ is associated with the risk of PJF. Little is known about the risk factors for PJF in case with the UIV at TLJ. Methods: Radiographic and clinical data of 63 consecutive patients who underwent instrumented fusion from sacrum to TLJ (T11, T12, and L1) for the treatment of ASD with a minimum 2-year follow-up were analyzed to identify the risk factors for PJF, which was defined as proximal junctional angle (PJA) ≥20°, fracture at UIV or UIV+1, failure of UIV fixation, myelopathy, or 'need for proximal extension of fusion. Results: During the average follow-up duration of 51.7 months, PJF developed in 23 patients (36.5%) at a mean of 9.3 months after surgery. Multivariate analysis revealed that age >70 years (odds ratio [OR]: 1.119), osteoporosis (OR: 4.459), and preoperative kyphotic PJA (OR: 1.138) were significant risk factors for the development of PJF. No PJF occurred in 14 patients lacking any risk factors. The last follow-up clinical results were significantly inferior in the PJF group than in the non-PJF group in terms of Oswestry Disability Index and Scoliosis Research Society-22 score. Conclusion: Age >70 years, osteoporosis, and PJA greater 0° were identified as significant risk factors for PJF. Therefore, the TLJ level can be considered as UIV selectively for patients younger than 70 years without osteoporosis and with lordotic preoperative PJA. Level of Evidence: 3 Abstract : Age >70 years, osteoporosis, and proximal junctional angle (PJA) greater 0° were identified as significant risk factors for PJF. Therefore, the TLJ level can be considered as uppermost instrumented vertebra selectively for patients younger than 70 years without osteoporosis and with lordotic preoperative PJA.